INTERVARIABLE INFLUENCE ANALYSIS OF HIERARCHY OF EFFECT (HOE) MODEL IN CROSS-BORDER E-COMMERCE (STUDY CASE: SHOPEE AND LAZADA) - Gabriella, Diyang Risma; Agus, Anna Amalyah (UI Scholars Hub, 2021)
Manuscript type: Empirical research Research aims: This study was conducted to analyze and develop the intervariable influence within the stages of HOE Model in CBEC context. Design/methodology/approach: Based on the Hierarchy of Effect (HOE) model which consists of the stages of customer progression of learning and decision-making as a response of their shopping experiences. A total research data of 1,651 respondents were collected through a structured questionnaire. SEM method was used to test the proposed research model. Research findings: HOE Model was found to vary based on the level of product cognition and platform involvement. Two case studies provide different results which occur due to the different shopping journey held by the customer from the stages of cognition and involvement to the decision of making a purchase. Theoretical Contribution/Originality: The less attention that was given to the customer behavior in CBEC context has driven the authors to analyze customer journey from product cognition to actual behavior stage in CBEC context. The modification towards previous research model is conducted to extend the analysis with a purpose to provide a full picture of the customer experience and the factors that influence their buying decision. Practitioner/Policy Implication: Provide insights to encourage parties involved for implementing strategic plans that could escalate market presence and competitiveness of Indonesia CBEC at the global trade. Research limitation/Implications: The authors extend the research model to actual behavior stage which creates a wider unexplored variables on the formation of perceived trust and the overall affective stage.